MS Vlkerfreundschaft . MS International Friendship - Knorr, Ulrike (Germany, 2005)
Verzio FF submission The documentary voyages along the Baltic coast to the Soviet Union on the GDR maiden cruise ship the "MS Völkerfreundschaft" (MS International Friendship). The filmmaker confronts the promises of distant destinations and the reality of limitations within the GDR. Leagues away from the currebt wave of "Ostalgia", she uses personal stories and recollections to present a different kind of case.